Strategi Digital Marketing Dalam Meningkatkan Penjualan Pada Usaha Clothing di Tokecangusedcloth - Arziel Pramudya; Ahmad Rizal Abdullah; Dwi Epty Hidayaty (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
This study aims to find out about the implementation of the digital marketing strategy used by TokecangUsedCloth in increasing its sales. Digital marketing is promotional activities and market search through online digital media by utilizing various means such as social networks. Before determining the media used for promotion, it is necessary to plan an advertising marketing idea and press release activities. This study uses descriptive research with a qualitative approach with the object of TokecangUsedCloth research. This research was conducted in March 2023. The types of data are primary data and secondary data. Data collection techniques in this study were observation to observe and directly record digital marketing strategies, interviews to obtain information about digital marketing strategies, and documentation to strengthen research data in the field. The results of the study show that TokecangUsedCloth uses digital marketing as its marketing medium and promotions by utilizing social media such as Instagram. In addition, TokecangUsedCloth uses social media to inform and communicate with consumers. However, there are still obstacles faced by TokecangUsedCloth in implementing digital marketing, namely an unstable internal connection. However, the impact arising from the implementation of digital marketing carried out by TokecangUsedCloth is that digital marketing can increase sales.